2022
DOI: 10.1155/2022/8627124
|View full text |Cite
|
Sign up to set email alerts
|

Settlement Characteristics of Split Grouting Pile Composite Foundation in Loess Areas

Abstract: Loess foundations often affect the stability of superstructures due to their insufficient bearing capacities; thus, reinforcement measures are crucial for mitigating the uneven settlement of foundations. This study aims to investigate the settlement characteristics of composite foundations for loess foundations reinforced by splitting grouting piles. First, split grouting tests were carried out on loess foundations. After the test piles reached the design strength, static load tests and geotechnical tests were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…At present, DCM piles have been widely used in the treatment of subgrade settlement distress caused by soft loess settlement 24 , 58 – 60 . We have carried out the application and practice of GPR technology in defect detection of DCM piles and quality evaluation of ground improvement based on the construction project of Anlin highway in Gansu Province, China.…”
Section: Resultsmentioning
confidence: 99%
“…At present, DCM piles have been widely used in the treatment of subgrade settlement distress caused by soft loess settlement 24 , 58 – 60 . We have carried out the application and practice of GPR technology in defect detection of DCM piles and quality evaluation of ground improvement based on the construction project of Anlin highway in Gansu Province, China.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the mechanical state of a pile can be roughly divided into elastic, elastic-plastic, plastic, and failed state according to the rebound rate of the pile. In some previous studies, the pile state was roughly divided into linear, plastic, and failure stages according to the change trend of the Q-S curves [18]. Here, the Golden Section approach is used to identify the mechanical state of the pile.…”
Section: Discussionmentioning
confidence: 99%
“…Wei et al [20] showed that the stress distribution of GPRS embankment is affected by the planar and spatial soil arch effects under dynamic load, and Liang et al [11] found that the existence of geogrids can reduce the influence of dynamic load on the arch effect. To improve the bearing capacity of loess foundations, Zhou et al [21] and Deng et al [22] investigated GRPS embankment for loess foundations reinforced by splitting grouting piles and grouted cement fly ash gravel (CFG) piles. The results show that the structure has good bearing capacity under static load.…”
Section: Introductionmentioning
confidence: 99%